Organization of independent work of higher education students using distance learning technologies - Ryabova, O. (Problems of Engineer-Pedagogical Education, 2021)
The problem of organizing independent work of higher education seekers is critical nowadays. Much attention is paid to the introduction of new technologies in the organization of classroom and independent work of students. In today's conditions, the leading place is occupied by the distance learning technologies for the organization of independent work. Independent work of students with the use of distance learning technologies becomes more guided by the teacher and more individualized, which motivates the student to gain new knowledge on their own initiative. The purpose of the article is to describe the organization of independent work of higher education students, who specialize in the discipline "First Premedical Aid", using the specially designed distance course, and also to evaluate its effectiveness. The distance course "First Premedical Aid" was developed using the MOODLE platform and contains general information about the course, as well as communicative, informational, and activity-based components. With the help of this distance course, the teacher guides the independent work of higher education students, increases their interest in the discipline, and encourages students to study independently. The individual and group tasks presented in the distance course allow students to acquire knowledge, skills and capabilities to provide premedical care to casualties in case of various emergencies, bring students closer to the real-life conditions of their professional activities. The evaluation of the effectiveness of the proposed organization of independent work for higher education students proved an increased quality of the learning outcomes of the "First Premedical Aid" course among those distance learning students who used distance learning technologies in comparison with the students using traditional learning methods. Further introduction of distance learning technologies into the pedagogical process is promising, which will increase the efficiency of the organization of students’ independent work and improve the quality of education.